HUBUNGAN PENGETAHUAN, KEBIASAAN MEMBACA NUTRITION FACTS DAN FREKUENSI KONSUMSI MAKANAN KEMASAN DENGAN STATUS GIZI LEBIH REMAJA PENGUNJUNG SUDIN PUSAR JAKSEL - Defita Amanda (2021)
Adolescents with overweight and normal nutritional status have similarity in frequency consumption of packaged foods and reading habits of nutrition labels. Knowledge is the primary guidance when reading nutritional labels which influence behavior in choosing packaged foods.This study aims to find out the relationship between knowledge and habits of reading nutrition facts and the frequency consumption of packaged foods with overweight status in adolescent visitors at sudin pusar jaksel. This research use cross-sectional design with accidental sampling technique. The selected sample was 38 adolescents aged 18-25 years. The data were collected using a questionnaire and measuring instruments microtoise and digital scales. The data tested using Chi Square test method. The results showed that knowledge of nutrition facts (p= 1,000), habits of reading nutrition facts (p= 0.235), and frequency of consumption of packaged foods (p= 1,000) were not related (p>0.05) with overweight status in adolescents. The majority respondents have sufficient knowledge of nutrition facts (73.7%) but did not obedient to reading nutrition facts (68.4%) so that is necessary to align knowledge with behavior in order to has real impact on the frequency consumption of packaged foods and nutritional status.